RENCANA TATA BANGUNAN DAN LINGKUNGAN (RTBL) DALAM MENATA RUANG KOTA - Nurfitriati, Ilva (Faculty of Law, Parahyangan Catholic University, 2015)
Urban society has a placed a considerable amount of hope in and holds great expectations of the Urban Planning Program (RTRWK) on RTRWK as the solution to urban planning problems. This program serves as a general guideline for urban planning, although much more detailed regulations are certainly required. The Building and Developmental Planning Program (RTBL) contains urban planning regulations that are in fact already in place despite its being much less popular and/or well known compared to its counterparts: RTRWK or even RDTR (Detailed Urban Space Management Program). Urban and environmental development planning can be one of the solutions for urban management and regulations in accordance with Law No. 26 of 2007 concerning Urban Planning, as well as government regulations for urban planning management. In this study, attempts are made to describe and explain how RTBL can be utilized as a so-called tandem solution to certain urban planning problems, after taking into consideration that various urban areas have distinct characteristics and priorities.